Meningkatkan Kompetensi Guru Berbasis Komunitas bagi MGMP SMP Kota Blitar - Miranu Triantoro; Udin Erawanto (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Teachers as the main factor in implementing learning need to improve their competence, both professional, pedagogic, personal and social competence. By having complete competence, the teacher will have the expected responsibilities based on laws and regulations. One of the teacher competencies that needs to be developed is writing a scientific article competence. Facts in the field show that many of the teachers have